Fetal intraabdominal umbilical vein varix: antenatal diagnosis and management. (17th January 2018) - Ozek, Murat Aykut; Calis, Pinar; Bayram, Merih; Karcaaltincaba, Deniz
Abstract: Objective: Fetal intraabdominal vein varix (FIUVV) is a sonographic finding with unknown prevalence. We aimed to point out this particular abnormality and review possible associations and complications which may arise. Method: We performed an unrestricted literature search via PubMed and included all cases diagnosed with FIUVV. Case presentation: A 24-year-old, gravida 1 para 0 woman was referred to our clinic with possible diagnosis of FIUVV. We confirmed the diagnosis and detailed sonogram was normal. Beyond the gestational age of 32 weeks, intruterine growth restriction became evident. Close fetal surveillance was performed. We did not detect any thrombus formation within the varix or signs of cardiac decompansation during these visits. Delivery was planned after completion of 37 weeks. A healthy baby weighing 2100 g was delivered and discharged without any complications. Conclusion: It is generally accepted that fetal anatomic survey is necessary after detection of FIUVV. Karyotyping could be performed for those cases associated with additional structural malformations. Close surveillance of fetal well being and growth is important. Possibility of thrombus formation within the varix should be kept in mind.